Exploring the geography of closing businesses in the crisis-stricken Athens city centre - Dimitris Kavroudakis; Dimitris Ballas; Vassilis Monastiriotis (European Regional Science Association (ERSA), 2013)
The economic crisis in Greece has affected almost all sectors of economy and the great majority of households. Its effects in trade and commerce activities are visible by the obvious transformation of down-town Athens city centre. This transformation includes a great number of closing business and/or relocation of others. The work presented in this paper is part of a wider project aiming to shed some light on the underlying mechanisms which affect business location, business closure and opening in the main commercial centre of Athens, at a time that it is under huge economic strain. As a starting point in this project, this paper makes use of a unique geographically coded database, collated through primary research by the authors and containing information on the specific location and type of retailer closures in crisis-stricken downtown Athens between 2011-2013, to provide an exploratory analysis of the emerging spatial and temporal patterns of business closure across the city centre. This, predominantly descriptive, analysis allows us to identify and discuss a number of patterns and hypotheses concerning the dynamics and determinants of retail closures during the economic crisis, revisiting relevant theories drawn from the wider literature on urban and location economics. In particular, we seek to analyse questions such as: what can we learn from the observed geography/patterns of closures about the underlying market functioning (or non-functioning?) What kind of shops survive in the crisis? Does agglomeration (still) matter? What are the locational (and co-location) characteristics that affect business survival and death? What kind of shops survive (in terms of types of activity, types of ownership, size of business, consumer catchment areas etc)? To what extent do closures of particular types of shops (e.g. a clothes retail shop) and businesses (e.g. a bank branch) increase the chances of closures of other types of shops (e.g. cafes, restaurants)? Does geographical location and type (e.g., corner shop versus middle-of-the-road shop, high-street shop versus neighbourhood shop etc.) matter and how? These kinds of questions are explored in this paper using appropriate data geovisualisation and statistical methods and in this way forming a background for the subsequent confirmatory analysis and hypothesis testing to be conducted in future work on the project.
Keywords: O18; R14; L81; R30; 330